PARENTING MEDIATION AND MONITORING: HOW FAMILY STRUCTURE SHAPES RESPONSES TO CHILDREN’S ONLINE SEXUAL HARASSMENT - Matković, Roberta; Vejmelka, Lucija; Ramljak, Tomislav (International Journal of Child, Youth and Family Studies, 2025)
Children from single-parent families may face greater challenges related to both internalized and externalized difficulties compared to those raised in two-parent households. The digital age adds further risks, with the need to protect children from online threats such as sexual harassment. This study examines parental mediation and response strategies in the context of child online sexual harassment, focusing on differences between single-parent and two-parent families. A nationally representative quantitative survey was conducted within the deSHAME2 project in Croatia, which involved 1,667 parents of school-age children. Using structured questionnaires and validated measurement scales, the study explored how parents engage in internet safety discussions with their children, their level of concern about online harassment, and the specific actions they take when faced with such incidents. Data were analyzed using nonparametric statistical methods, including the Mann-Whitney test and Spearman’s rank correlation. Findings reveal that while single-parent and two-parent households adopt largely similar parental mediation strategies and responses to online risks, parents in two-parent families were more likely to engage in discussions with their children when a problem was identified. These results suggest that parenting behaviors such as communication, monitoring, and readiness to act may play a more significant role in child online protection than family structure alone. By highlighting these patterns, the study emphasizes the importance of systematic education and support programs for all parents. Fostering proactive parental involvement in and open communication about online safety remain essential steps in reducing children’s exposure to digital risks, regardless of family composition.